Aerodynamic Simulation on Roof for 3,000 Watt Electric Car With Ansys R1 2022 Modeling - Cecep Hamidi Hamidi; Ade Sunardi; Ryan Ariansyah (Journal of Global Engineering Research and Science, 2022)
Technological advances in electronics and machinery, especially in the design of electric motors, are the first step in the development of electric cars. The body is the main part of the car that functions as a construction protection and electrical panel from external factors such as sunlight, rain, and others. In this study, an analysis of the body and roof of an electric vehicle will be carried out to determine the flow of fluid or air that occurs in the car body. How to design the body and roof of a car, how is the air velocity vector that occurs around the roof of the car at speeds of 10 km/hour, 40 km/hour, and 70 km/hour. Before the method starts, literature studies, data collection, the process of designing an electric car body model, aerodynamic analysis through the ansys R1 2022 software, taking test results and conclusions, simulation data analysis techniques are conducting searches on the frontal area, entering geometry in the ansys model, setting sizes and setting of mesh clauses and airflow calculations. The results of the aerodynamic simulation of speeds of 10 km/hour, 40 km/hour, and 70 km/hour. There are parts or positions that block the air the most as shown in red, while those with the least air resistance are dark blue, the maximum speed results are shown in dark blue, while the minimum speed is shown in red so that the area has the greatest resistance. air.